1995
DOI: 10.1177/0042085995030003003
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Rural Prospective Teachers toward Teaching in Urban Schools

Abstract: Educational inequity in urban schools is due in part to an inability to attract and retain fully educated and experienced teachers. According to data gathered in a study of rural teacher candidates, they have little knowledge or experience about teaching in urban schools. Their information comes primarily from secondary sources rather than from direct experiences. Although they lack both knowledge and experience, these participants reported that they would seek employment in urban schools to be assured of a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Fry and McKinney (1997) found that 6 of 10 White female preservice teachers who completed an urban-based field experience stated they would teach in an urban school only if they could not find another job elsewhere. Likewise, Gilbert (1995) found that most of 193 prospective teachers in a rural university who completed a demographic survey with open-ended items about urban schools would teach in an urban school only if they had to find a job. The pervasiveness of deficit views and stereotypes greatly affects the willingness of teacher candidates to teach in culturally diverse and urban contexts.…”
Section: Changes In Preservice Teachers’ Views About Diversitymentioning
confidence: 99%
“…Fry and McKinney (1997) found that 6 of 10 White female preservice teachers who completed an urban-based field experience stated they would teach in an urban school only if they could not find another job elsewhere. Likewise, Gilbert (1995) found that most of 193 prospective teachers in a rural university who completed a demographic survey with open-ended items about urban schools would teach in an urban school only if they had to find a job. The pervasiveness of deficit views and stereotypes greatly affects the willingness of teacher candidates to teach in culturally diverse and urban contexts.…”
Section: Changes In Preservice Teachers’ Views About Diversitymentioning
confidence: 99%
“…The interaction with NNES teacher educators is surely helpful in this respect. This is especially important in the light that white pre-service teachers (most of my students are white) are reported to have little cross-cultural knowledge and experience (Gilbert, 1995;McIntyre, 1997;Sleeter, 2000). Yet they still consist of the majority of the teaching force and are likely to run into immigrant/minority students in their teaching careers.…”
Section: Reconceptualizing Diversitymentioning
confidence: 99%
“…Adding to this, they bring little to no cross-cultural background, knowledge, or experience. Therefore, education around issues of cultural competence is complicated (Barry & Lechner, 1995;Gilbert, 1995;McIntyre, 1997;Valli, 1995).…”
Section: Preparing Culturally Competent Educatorsmentioning
confidence: 99%